Comparative transcriptome analysis revealed genes involved in the sexual size dimorphisms and expressed sequence tag-Simple Sequence Repeat loci validation in Odorrana graminea - Li, Hanyu; He, Wenke; Wang, Tonghang; Cui, Chong; Zhang, Jie; Chen, Xiaohong (Frontiers in Ecology and Evolution, 2023)
Sexual size dimorphism (SSD) is widespread among animals and is characterized by differences in body size between sexes. Previous studies suggested SSD might reflect the adaptations of particular sexes to their specific reproductive or ecological roles. The large green cascade frogs (Odorrana graminea) exhibit obvious SSD that females are nearly twice the body size of males. However, the molecular mechanisms underlying SSD of O. graminea are still unknown. In the present study, we first obtained nearly 5Gb of the transcriptome data through Illumina sequencing, and the de novo transcriptome assembly produced 189,868 unigenes of O. graminea. A total of 774 significantly sex-differentially expressed genes (DEGs) were identified. Of which, 436 DEGs showed significantly higher expression levels in females than those in males, whereas 338 DEGs showed significantly lower expression in females than those in males. We also found ten sex-differentially expressed genes related to energy metabolism between sexes of O. graminea, and these DEGs were related to the estrogen signaling pathway, oxidative phosphorylation, fatty acid biosynthesis, gastric acid secretion, and nitrogen metabolism. We found that the differences in energy metabolism and steroid hormone synthesis might be the main driving force leading to the sexual growth dimorphism of O. graminea. In addition, a total of 63,269 potential EST-SSR loci and 4,669 EST-SSR loci were detected and validated in different populations of O. graminea and other species within Odorrana. The assembled transcriptome will facilitate functional genomic studies of O. graminea and the developed EST-SSR markers will contribute to the population genetics of the species within Odorrana. The sex-differentially expressed genes involved in energy metabolism might provide insights into the genetic mechanisms underlying the SSD of O. graminea.